Improving Nursing Students’ Knowledge about Health Myths in Indonesia - Anung Ahadi Pradana; Ismail Fahmi; Casman Casman; Nani Asna Dewi; Alfunnafi’ Fahrul Rizzal; Muhammad Chandra; Nur’aini Nur’aini (Journal of Community Empowerment for Health, 2023)
Health myths are one of the factors that can hinder the achievement of government programs in the health sector. The resistance that arises from the community can be even greater if the believed myths have taken root in social life and are  considered to have magical elements in their implementation. To change the errors in people’s health beliefs in society,  health workers are important in providing proper health education and health literacy to all levels of society. Based on the  problems found, the team’s goal was to improve nursing students’ knowledge about health myths in Indonesia. This activity was implemented for 199 nursing students from 7 provinces (DKI Jakarta, West Java, Banten, Jambi, East Java, Central Java, and Southeast Sulawesi) online through Zoom meetings. This activity was the final series of activities conducted by the Institute of Training, Education and Research, Nurse Share Idea (NSID) about health myths that exist in Indonesia, while the implementation of this series of activities was done from November 2020 to August 2021. The results of the Wilcoxon testing of the activities had the value of sig = 0.002 (<0.005), which means that the activities have had a significant and positive impact on improving nursing students’ knowledge about health myths in Indonesia. Four of the 14 topics of understanding  health myths were decreased. These four topics are related to myths in nursing care. The results indicated that activities could increase participants’ knowledge of health myths. However, nurses still experience confusion preventing myths in implementing nursing care for patients. Other activities can focus on increasing efforts to counteract myths in implementing nursing care.